Penerapan Seni Kaligrafi dalam Meningkatkan Kemampuan Menulis Arab Siswa Kelas VI SD Islam Yayasan Pendidikan Loktuan Bontang Utara Tahun Pelajaran 2024/2025 - Irpan, Irpan; Syamsiar, Syamsiar (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
Abstrack _ The purpose of this study was to determine the extent to which the application of calligraphy art can improve students' Arabic writing skills. This type of research is classroom action research (CAR) which is carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The methods used are qualitative and quantitative approaches. The instruments used in data collection include observation, interviews, written tests, and documentation. Data analysis techniques are carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the application of calligraphy art has a positive effect on improving students' Arabic writing skills. This can be seen from the increase in students' average scores from cycle I to cycle II and the increase in students' interest and accuracy in writing Arabic letters. The conclusion of this study is that calligraphy art is effective as a learning method in improving students' Arabic writing skills in grade VI. The application of calligraphy no only improves learning outcomes, but also fosters an attitude of love for the beauty of Arabic writing.